The Effect of Service Quality In Shaping Consumer Purchase Intention With Positive Perception As A Mediating Variable (Study In CitraGarden City Jakarta) - Tony Ngadimun; Teofilus Teofilus; Endi Sarwoko (Dinasti Publisher, 2024)
The aim of this research is to investigate how the service quality of a product influences consumer purchase intentions through positive perceptions as a mediator. The research aims to understand whether consumers tend to buy a product because they have a positive perception of the quality of the service provided, and how this positive perception mediates the relationship between service quality and purchase intention. In this context,